1988
DOI: 10.1063/1.100135
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and the band structure of InAsSb strained-layer superlattices

Abstract: Infrared photoluminescence measurements were performed on InAs0.13Sb0.87 /InSb strained-layer superlattices. In thick layered structures we observed very low energy transitions proving that a type II superlattice occurs in the InAsSb system. Band structures were calculated based on estimates of the band offsets and strain shifts obtained from the photoluminescence data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Our result is consistent with optical studies by Kurtz et d [ 7 ] and a tight-binding calculation [S]. Under these conditions, n-type doping again gives carriers in the smaller-band-gap InAsSb channel but now the p-type doping results in creating light holes in the InSb.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our result is consistent with optical studies by Kurtz et d [ 7 ] and a tight-binding calculation [S]. Under these conditions, n-type doping again gives carriers in the smaller-band-gap InAsSb channel but now the p-type doping results in creating light holes in the InSb.…”
Section: Introductionsupporting
confidence: 92%
“…The mobilities achieved are disappointingly low for such low-mass carriers. These mobilities may be attributed to the low carrier densities necessitated by the shallow confinement in the InSb channel for the holes (estimated to be 60 meV) [7].…”
Section: Samples Were Grown Onmentioning
confidence: 99%
“…For an InAs 1Ϫy Sb y /InAs 1Ϫx Sb x junction in the Sb-rich limit ͑large x and yϭ1͒, initial optical measurements supported an unstrained VBO of (0.36-0.41)(1Ϫx) eV. 944,945 In the As-rich limit ͑small x and yϭ0͒, on the other hand, Li et al concluded from fits to magneto-optical spectra that the top of the InAsSb valence band appeared lower than that in InAs (Ϫ0.84x eV). 946,947 That result implied a substantial CBO and negative VBO for small x.…”
Section: G Gasbõinsb and Inasõinsbmentioning
confidence: 93%
“…A type II offset occurs when the lowest energy transition is no longer between energy levels within the smaller bandgap material and the lowest energy transition is spatially indirect. GaP/GaAsP and the Sb-rich InAsSblInSb SLSs are type II superlattices [3,4]. A type II offset is illustrated in Fig.…”
Section: Band Offset Effects On Sls Energy Levelsmentioning
confidence: 99%
“…3 where the lowest energy electron level occurs in the InAsSb layer and the highest energy hole level occurs in the InSb layer of the SLS. The presence of a type II band offset in InAsSblInSb SLSs allows for the design of very long (> 12 J,lm) wavelength devices [4][5][6]. A semimetal occurs for a InAs/GaSb SLS where the conduction band of InAs is below the valence band of GaAsSb.…”
Section: Band Offset Effects On Sls Energy Levelsmentioning
confidence: 99%